The development of energy risk framework for retrofitting project - Nikman Lee, Mohammad Syabilee (2021)
Energy demand in existing building growths every year compared with new building. The growth of energy consumption on existing building is significantly soaring throughout every year due to the degradation of energy efficiency and near-end life expectancy of building components. Energy retrofit is proven to improve energy efficiency at the expense of numerous risks as early in pre-construction project. Thus, the influences of risk facing by stakeholders to achieve optimum design strategies granting a huge effect in retrofit project. This research aims to address risks in retrofit project during pre-construction stage by determining the potential risk factors and the relationship with the retrofit elements. This research used convergent-parallel mixed-method within the context of qual-quan research design to administer semi-structured interviews and questionnaires to obtain information from internal stakeholders. With the aid of Computer-Assisted Qualitative Data Analysis Software (CAQDAS), Atlas.Ti version 7, the qualitative data were coded, categorized, and analysed obtained from six respondents. The Statistical Package for Social Science (SPSS) were used for analysing quantitative data collected from 66% of respondents out of 198 samples. The analysis revealed that two critical risk factors was found under planning and design phase. In planning phase, the most critical factor is related with the tenant cooperation in post-planning. The contribution of this risk is influences by the policies, regulation, human factor, and uncertainty factor elements. Likewise, the risk in design phase that require critical concern is related with inaccurate of energy model. It shows that the risk is influences by technologies, uncertainty factor and client expectation elements. The highlighted risks demonstrate the correlation with the retrofit elements to achieve optimum energy efficiency design through developed framework model. The develop framework model was validated across ten respondents and proven to assist construction industry to achieve optimum design strategy by assessing the highlighted risk factors and elements. The validation process in framework is conducted through expert panel in retrofit project and analyse using Krippendorff alpha reliability method.